Recent Advances in the Palladium Catalyzed Suzuki–Miyaura Cross-Coupling Reaction in Water - Chatterjee, Anamitra; Ward, Thomas R. (Catalysis letters, 2016)
The palladium-catalyzed Suzuki–Miyaura cross-coupling reaction of organic halides with boronic acids is one of the most versatile methods for the synthesis of biaryls. Green chemistry is a rapidly developing new field that provides us a proactive avenue for the sustainable development of future science and technologies. When designed properly, clean chemical technology can be developed in water as a reaction medium. The technologies generated from such green chemistry endeavours may often be cheaper and more profitable. This review covers the literature on palladium-catalysed the Suzuki–Miyaura cross-coupling reaction in water. Graphical Abstract